Gastroduodenal Mucosal Injury Profile in Long-Term Low-Dose Aspirin Users and Its Influencing Factors - Franciscus Ari; Ari Fahrial Syam; Dadang Makmun; Suhendro Suhendro (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Background: Low-dose aspirin is the most common drug used for prevention of cardiovascular and cerebrovascular events. Long-term aspirin therapy can induce gastroduodenal mucosal injury, even in a very low dose (10 mg daily). The frequency of gastroduodenal injuries among long-term low-dose aspirin users in Indonesia is currently unknown. The aim of this study is to determine the prevalence of gastroduodenal mucosal injury, endoscopic findings, and influencing factors among long-term low-dose aspirin users in Cipto Mangunkusumo Hospital.Method: This study was a cross-sectional study conducted in Cipto Mangunkusumo Hospital, Jakarta. Subjects were patients aged ≥ 18 years old who had been using low-dose aspirin (75-325 mg) for at least the preceding 28 days. Ninety-five subjects were recruited consecutively in the period of December 2015 – April 2016. History taking, upper endoscopic examination, and histopathology examination for Helicobacter pylori infection were performed in all subjects. Endoscopic findings such as erosions and ulcers were assessed as mucosal injuries. Data were analysed to find prevalence, bivariate analysis (Chi-square test), and multivariate analysis (logistic regression test).Results: Mucosal injury was found in 49 subjects (51.6%; 95% CI: 41.6–61.7%), mucosal erosion in 38 subjects (40%; 95% CI: 30.2–49.9%) and ulcers in 11 subjects (11.6%; 95% CI: 5.2–18.0%). Only 44.9% patients with mucosal injury had dyspepsia symptoms. Double antiplatelet therapy increased the risk of mucosal injury (OR = 3.3; 95% CI: 1.3–8.5). However, proton pump inhibitor (PPI) decreased the risk of mucosal injury (OR = 0,2; 95% CI: 0,04 – 0,60).Conclusion: Gastroduodenal mucosal injury was found in more than half of long-term low-dose aspirin users. Double antiplatelet therapy increased the risk of mucosal injury, while PPI effectively reduced the risk.